The 1.5 Generation : Becoming Korean American in Hawaii - Danico, Mary Yu (University of Hawaii Press, 2004)
The "1.5 generation" (Ilchom ose) refers to Koreans who immigrated to the United States as children. Unlike their first-generation parents and second-generation children born in the United States, 1.5ers have been socialized in both Korean and American cultures and express the cultural values and beliefs of each. In this first extended look at the 1.5 generation in Hawaii, Mary Yu Danico attempts to fill a void in the research by addressing the social process through which Korean children are transformed from immigrants into 1.5ers. Dozens of informal, in-depth interviews and case studies provide rich data on how family, community, and economic and political factors influence and shape Korean and Korean American identity in Hawaii. Danico examines the history of Koreans in Hawaii, their social characteristics, and current demographics. Her close consideration of socio-cultural influences firmly establishes the 1.5 generation in the mainstream discussion of identity formation and race relations.